Gender-based needs and the global governmentality of care and domestic labor - Beier, Friederike (Frontiers in Political Science, 2025)
Addressing unpaid care and domestic labor is an essential gender-based need for feminist scholarship, as its unequal distribution is one of the main factors behind gender inequality. This study examines the United Nations (UN) discourse on unpaid care and domestic labor through a Foucauldian governmentality framework, analyzing policy documents since 2010. It investigates how international strategies address gender-based needs to recognize unpaid care and domestic labor and whether they contribute to transforming the gendered division of labor. Employing Foucauldian Discourse Analysis, the research assesses the rationalities, technologies and power effects embedded in UN policies. The findings reveal that the UN primarily focuses on the reduction, quantification, and economic valorization of unpaid care labor, reinforcing economic rationalities that ultimately fail to challenge the structural subordination of reproductive labor. The technocratic governance depoliticizes gender interests, prioritizing paid labor as an empowerment strategy while neglecting broader feminist demands for structural transformation. The study further argues that the feminist literature on gender needs and the political economy of reproductive labor constructs unpaid care and domestic labor as a burden, contributing to its commodification and devaluation. The right to self-determined time is discussed as an alternative framework for conceptualizing gender-based needs.